2003
DOI: 10.1037/0012-1649.39.2.292
|View full text |Cite
|
Sign up to set email alerts
|

Initial behavior outcomes for the PeaceBuilders universal school-based violence prevention program.

Abstract: PeaceBuilders is a universal, elementary-school-based violence prevention program that attempts to alter the climate of a school by teaching students and staff simple rules and activities aimed at improving child social competence and reducing aggressive behavior. Eight matched schools (N Ͼ 4,000 students in Grades K-5) were randomly assigned to either immediate postbaseline intervention (PBI) or to a delayed intervention 1 year later (PBD). Hierarchical linear modeling was used to analyze results from assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
128
0
11

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(140 citation statements)
references
References 61 publications
1
128
0
11
Order By: Relevance
“…Social skills' development in general constitutes a conquered domain of several mental health promotion programs pursuing general social competence (Beelmann & Lösel, 2006;Domitrovich, Cortes, & Greenberg, 2007;Flannery et al, 2003;Mishara & Ystgaard, 2006), but the specific friendship skills examined in our study did not result to higher improvement of the intervention group.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…Social skills' development in general constitutes a conquered domain of several mental health promotion programs pursuing general social competence (Beelmann & Lösel, 2006;Domitrovich, Cortes, & Greenberg, 2007;Flannery et al, 2003;Mishara & Ystgaard, 2006), but the specific friendship skills examined in our study did not result to higher improvement of the intervention group.…”
Section: Discussionmentioning
confidence: 40%
“…Concerning implementation fidelity-"the degree to which teachers and other program providers implement programs as intended by the program developers" (Dusenbury et al, 2003: 240), which plays a critically important role in the evaluation of interventions (Durlak & DuPre, 2008;O'Donnell, 2008) we took the following measures, similar to ones used in relevant studies (Brackett et al, 2012;Flannery et al, 2003;Mishara & Ystgaard, 2006): 1) Clear implementation guidelines were included in the program's Teacher's…”
Section: Implementation and Implementation Fidelitymentioning
confidence: 99%
“…Of these interventions, four had an evaluation in which the research design criteria for Tiers I-III were met, yet there were no statistically significant positive results on any of our outcomes of interest: Girls in the Game (Bohnert and Ward, 2013), Lessons in Character (Hanson et al, 2012), Peer Group Connection (Johnson, Simon, and Mun, 2014), and Teacher-Child Interaction Training (Fernandez et al, 2015). In addition, four interventions had an evaluation in which the research design criteria for Tiers I-III were met, and there was a statistically significant negative result on an outcome interest: Creating a Peaceful School Learning Environment (Fonagy et al, 2009), on a measure of school climate and safety; Guiding Responsibility and Expectations for Adolescents for Today and Tomorrow (Farrell, 2008), on a measure of interpersonal competencies; PeaceBuilders (Flannery et al, 2003), on a measure of interpersonal competencies; and Social Problem Solving (Gottfredson, Jones, and Gore, 2002), on a measure of academic attainment. We have not included these eight interventions on our list of evidence-based interventions.…”
Section: Search Resultsmentioning
confidence: 99%
“…Some recent meta-analyses suggest that universal school-based approaches to preventing aggressive behavior can be effective (Hahn et al 2007;Wilson and Lipsey 2007). Other rigorous studies and meta-analyses have shown significantly positive effects on some outcomes of interest but indeterminate or non-statistically significant effects on other outcomes, no significant effects at all, and even potentially negative effects (e.g., CPPRG 1999; Grossman et al 1997;Flannery et al 2003, Park-Higgerson et al 2008, Merrell et al 2008). …”
Section: Universal School-based Social and Character Development Progmentioning
confidence: 99%